Radiomics and machine learning applied to STIR sequence for prediction of quantitative parameters in facioscapulohumeral disease - Colelli, Giulia; Barzaghi, Leonardo; Paoletti, Matteo; Monforte, Mauro; Bergsland, Niels; Manco, Giulia; Deligianni, Xeni; Santini, Francesco; Ricci, Enzo; Tasca, Giorgio; Mira, Antonietta; Figini, Silvia; et al. (Frontiers in Neurology, 2023)
Purpose : Quantitative Muscle MRI (qMRI) is a valuable and non-invasive tool to assess disease involvement and progression in neuromuscular disorders being able to detect even subtle changes in muscle pathology. qMRI sequences are, however, not commonly available in most of the clinical centers. The aim of this study is to evaluate the feasibility of using a conventional short-tau inversion recovery (STIR) sequence to predict fat fraction (FF) and water T2 (wT2) in skeletal muscle introducing a radiomic workflow with standardized feature extraction combined with machine learning algorithms. Methods : Twenty-five patients with facioscapulohumeral muscular dystrophy (FSHD) were scanned at calf level using conventional STIR sequence and qMRI techniques. We applied and compared three different radiomics workflows (WF1, WF2, WF3), combined with seven Machine Learning regression algorithms (linear, ridge and lasso regression, tree, random forest, k-nearest neighbor and support vector machine), on conventional STIR images to predict FF and wT2 for six calf muscles. Results : The combination of WF3 and K-nearest neighbor resulted to be the best predictor model of qMRI parameters with a mean absolute error about ± 5pp for FF and ± 1.8ms for wT2. Conclusion : This pilot study demonstrated the possibility to predict qMRI parameters in a cohort of FSHD subjects starting from conventional STIR sequence.